Experimental analysis of wave-induced vertical bending moment in steep regular waves. (May 2022) - Bouscasse, B.; Merrien, A.; Horel, B.; De Hauteclocque, G.
Abstract: Recent studies have benchmarked the prediction of the wave vertical bending moment (VBM) of ships in waves and found significant scatter among the numerical codes. A long series of tests with segmented hulls have been reported in the literature over the past 70 years to assess the vertical bending moment. However, alongside the improvement in numerical tools and the modeling of ships' internal loads, the scientific community still requires accurate experimental data measured in steep waves (ratio of wave height H to wavelength λ, H/ λ =  0.1) where the ship behavior and loads are modified by non-linearities. Thus, in order to validate simulation codes, and to establish criteria and requirements that make ships safer to sail in severe sea conditions, some experiments were carried out in the 50 m × 30 m × 5 m hydrodynamic and ocean engineering tank of the Ecole Centrale Nantes. A 1/65th scaled model of a 6750-TEU containership was used. The ship was moored and several combinations of wavelength and wave height were tested. The present experiments were performed on a segmented hull with a 6DOF load sensor located close to amidship, where some measurements were available from previous studies. The design, which did not use strain gauges, was done specifically to increase the first structural mode frequency and the stiffness of the model in order to reduce and make it possible to filter out hydro-elastic effects. The model motion was measured through a Qualisys IR tracking system and accelerometers were located on the fore and aft of the beam. Also, each of the 9 segments is equipped with a 3DOF dynamometer to measure the hydrodynamic loads on the hull. A mathematical description of the relations between the hydrodynamic forces, the load measurements and the internal forces is given in the paper. This makes it possible to retrieve the hydrodynamic loads on the segments and then to compute the shear force and bending moment discretized at each intersegment all over the ship length. Particular care was paid to the reproducibility and repeatability of the tests. The experimental setup and the measured data are presented in the paper. Hydrodynamic loads are reconstructed and the obtained VBM is compared with the 6DOF sensor measurement. The non-linear effects of increasing the wave steepness on motions and bending moment are discussed.